Gemcitabine enhances rituximab‐mediated complement‐dependent cytotoxicity to B cell lymphoma by CD20 upregulation. Issue 5 (7th April 2016) - Hayashi, Kazumi; Nagasaki, Eijiro; Kan, Shin; Ito, Masaki; Kamata, Yuko; Homma, Sadamu; Aiba, Keisuke
Abstract : Although rituximab, a chimeric monoclonal antibody that specifically binds to CD20, has significantly improved the prognosis for diffuse large B cell lymphoma (DLBCL), one‐third of DLBCL patients demonstrate resistance to rituximab or relapse after rituximab treatment. Thus, a novel approach to rituximab‐based treatment is likely to be required to improve the efficacy of DLBCL treatment. As complement dependent cytotoxicity (CDC) is a key mechanism mediating rituximab's tumoricidal activity, rituximab binding to CD20 on tumor cells is a critical factor for effective rituximab‐based treatments against DLBCL. We found that gemcitabine (GEM), but not lenalidomide (LEN) or azacitidine (AZA), can upregulate CD20 expression in TK and KML‐1 cells, two human DLBCL cell lines. Treatment of TK and KML‐1 cells with GEM enhanced CD20 expression at both the mRNA and protein levels. CD20 upregulation by GEM treatment was accompanied by increased rituximab binding to CD20. In TK cells, GEM treatment synergistically increased rituximab‐mediated CDC activity in a dose‐dependent manner. In KML cells, GEM treatment also induced upregulation of complement regulatory proteins, possibly leading to resistance to CDC. Treatment with LEN, a drug that did not upregulate CD20, did not enhance rituximab‐mediated CDC activity. GEM treatment activated nuclear factor‐kappa B (NF‐ k B) signaling in these cells. Furthermore, a specific inhibitor to NF‐ k B suppressed GEM‐induced CD20 upregulation, indicating that GEM‐induced NF‐ k B activation is closely associated with CD20 upregulation. These results suggest that when used in combination, GEM might enhance the antitumor efficacy of rituximab against DLBCL due to its unique ability to upregulate CD20. Abstract : Gemcitabine treatment of diffuse large B cell lymphoma (DLBCL) cells induces up‐regulation of surface CD20 expression in vitro . Combined treatment with gemcitabine and rituximab elicits high antitumor activity to DLBCL cells because of enhanced binding of rituximab to CD20.